The river meeting the sea: A qualitative exploration of the healthcare transition experiences of adolescents and young adults living with rare renal disorders and their parents - Melissa Kinch; Thilo Kroll; Suja Somanadhan (PLoS ONE, 2026)
Background Rare renal disorders are a group of complex conditions that can lead to progressive kidney failure and lifelong multi-system complications. Upon reaching young adulthood, adolescents and young adults must navigate the healthcare transition between paediatric and adult services. This process serves to bridge the gap between health services and provide adolescents and young adults with developmentally appropriate support to manage adult life with their condition. However, this process can prove challenging for adolescents and young adults with rare renal disorders, a research area that is currently under explored. Aim To explore the experiences of adolescents and young adults and parents living with a rare renal disorder and undergoing healthcare transition. Design Qualitative descriptive study, using reflexive thematic analysis. Results reported according to the COnsolidated Criteria for REporting Qualitative research (COREQ) checklist. Methods Twenty eight in-depth interviews were conducted, with 17 parents and 11 adolescents and young adults with rare renal disorders. Results Five themes were developed: 1. the complex and ever-changing nature of rare renal disorders, 2. preparing to move on, 3. understanding the person, 4. building support networks, and 5. care coordination, consistency, and communication. Adolescents and young adults and their parents recognised the need for individualised, collaborative, and holistic approaches to healthcare transition, emphasising the need for comprehensive support that acknowledges other areas of adolescents and young adults lives, including educational transitions, peer connection and psychological support. Conclusion This study emphasises the dynamic interplay between health and social systems when planning healthcare transition. This study offers valuable insights into healthcare transition in rare renal disorders. Findings provide a foundation for future research and can inform practice, policy and the development of future healthcare transition interventions. Patient or Public Contribution Two adolescents and one parent from a rare-disease advisory group provided input on the study materials.